THE USE OF INFORMATION COMMUNICATION TECHNOLOGY: A SURVEY STUDY IN SELECTED TERTIARY INSTITUTIONS’ LIBRARY IN KADUNA STATENIGERIA - Sani Murtala Ridwan (European Scientific Journal, ESJ, 2015)
Information Communication Technology is those inventions which facilitate easy and speedy dissemination and retrieval of information on a large scale. These include radio, television, cable satellite, computer, telephone, Fax machines, and Internet. The various Information Communication Technologies can be used to encompass all forms of technology used in the process of acquiring, storing, processing, and distributing information by electronic means. This paper has conducted survey on Information Communication Technology in selected tertiary institutions’ libraries in Kaduna state-Nigeria. Recommendations for functional I.C.T. use in tertiary institutions’ libraries in Kaduna state- Nigeria have also been given.